Pilates and telomere dynamics: A 12-month longitudinal study. (April 2022) - Nickels, Matt; Mastana, Sarabjit; Denniff, Matthew; Codd, Veryan; Akam, Elizabeth
Abstract: Telomeres are dynamic structures that appear to be positively influenced by healthy lifestyle factors such as exercise. Pilates is an increasingly popular exercise modality that is reported to exert beneficial physiological effects in the body, although the cellular mechanisms are poorly understood. The aim of the present study was to investigate the influence of Pilates exercise on telomere length. This longitudinal study followed experienced female Pilates practitioners (n = 11, 50.8 ± 7.5 years) and healthy age- and sex-matched sedentary controls (n = 11, 49.3 ± 6.1 years) over a 12-month period. Leukocyte telomere length was quantified using qPCR. Circulatory inflammatory markers, mRNA gene expression, body composition, physical performance, and mental well-being were also assessed. Telomere length was comparable between Pilates practitioners and controls at baseline (Pre) and 12-months (Post) (p > 0.0125). Pilates practitioners displayed enhanced mRNA gene expression of antioxidant enzymes (SOD2 and GPX1), and lower body fat percentage and visceral fat rating, compared with sedentary controls (p < 0.0125). Over the 12-month longitudinal period, Pilates participants significantly increased dynamic balance (p < 0.05). In conclusion, long-term Pilates participation does not appear to influence telomere length. Nonetheless, Pilates exercise appears to increase antioxidant enzyme gene expression, effectively manage body composition, and improve dynamic balance. Clinical Relevance: Pilates can upregulate SOD2 and GPX1 mRNA expression. Pilates can be utilised to effectively manage body composition. Continued Pilates exercise can improve dynamic balance in experienced practitioners. Pilates exercise does not appear to regulate TL.